Visual pollution and statistical determination in some of Karrada district main streets /Baghdad (Journal of Engineering, 2013)
This study objective is to identify the visual pollution in Karrada district main streets as an example of main streets in Baghdad, the public opinion about each pollutants, solutions to reduce and eliminate the pollution were suggested as well. In order to accomplish this objective different methods were used, 16 pollutants were selected, pictures of each pollutants were taken and a questioner were distributed randomly for 270 people to evaluate the public opinion with statistical methods. Garbage, their disposal and storage areas took the first two places as the highest offensive pollutants. The people showed that they find long lines of vehicles, debris and generators appearance ranked third, fourth and fifth respectively .This research showed that more than 70 percent of people are against the militarization of society and they consider any existence of heavy military machinery or personal is highly offensive issue. Other pollutants such as street sellers, beggars, and crossed wires considered as moderately offensive. Car parking in inappropriate places, badly trimmed trees, large billboards in the streets and the buildings criteria considered slightly offensive. The shops billboards and cellular phone and internet towers were considered the least offensive pollutants. Major solutions is to enhance the municipality management in both planning and operation methods relayed to pollution removal, running awareness campaigns to educate the people about the visual pollution effects and how to reduce it and reduce the military appearances in the city